Aluminum-tantalum-modified high-nickel ternary positive electrode material as well as preparation method and application thereof

By introducing aluminum-tantalum metal nanocoating on the surface of high-nickel ternary cathode material and combining high-temperature heat treatment, the shortcomings of high-nickel cathode material in terms of structural stability and safety are solved, and its electrochemical performance is improved and the battery is better stable.

CN119601649AActive Publication Date: 2025-03-11INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311167841.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

The existing high-nickel ternary cathode materials have shortcomings in surface side reactions, structural stability and safety, and conventional coating methods are difficult to effectively improve their electrochemical properties.

Method used

By uniformly and controllably introducing aluminum-tantalum metal nanocoating on the surface of high-nickel ternary positive electrode material, combining the non-aqueous solvent environment and high-temperature heat treatment, the chemical reaction between the surface-covered species and the high-nickel positive electrode is regulated to form a structurally stable aluminum-tantalum metal modified surface.

Benefits of technology

The surface physical and chemical performance regulation and optimization of high-nickel cathode materials has been achieved, which improves its electrochemical stability and safety, while also having the advantages of low cost, reliability and large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601649A_ABST
    Figure CN119601649A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum-tantalum-modified high-nickel ternary positive electrode material as well as a preparation method and application thereof. According to the invention, starting from the synthesis control of a solution phase, a nano coating containing aluminum and tantalum metal is firstly constructed on the surface of the high-nickel ternary positive electrode material, and then a chemical reaction between the positive electrode material and the surface coating is promoted through further high-temperature heat treatment, so that a surface structure with good stability and high charge transfer capability is obtained; therefore, the stability of the positive electrode material is remarkably improved, and the positive electrode material with high specific capacity and good cycling stability is obtained. And meanwhile, the method provided by the invention can fully meet the requirement of amplified production on the premise of ensuring no additional damage to the high-nickel ternary positive electrode material, has the advantages of low cost, high reliability and the like, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material technology and relates to a high-stability high-nickel ternary positive electrode material modified with aluminum-tantalum metals, and a preparation method and application thereof. Background Art

[0002] The continuous upgrading of portable electronic devices and new energy vehicles has put forward higher and higher requirements on the performance of lithium-ion batteries. High-energy lithium-ion batteries with high energy density, long cycle life, good safety and low cost have become one of the goals that researchers are developing and pursuing.

[0003] As one of the core components of lithium-ion batteries, cathode materials play a key role in the overall performance of batteries. x Co y M 1-x-y O2, M=Mn or Al, x≥0.6) has become the focus of research due to its high energy and power density. In this system, as the Ni content increases, its capacity increases, but it is also accompanied by more serious surface side reactions, worse structural stability and greater safety risks. Based on this, regulating the surface interface of the positive electrode material and developing high-nickel ternary positive electrode materials with good cycle performance and high safety performance has become one of the research hotspots in the field of positive electrode materials for lithium-ion batteries.

[0004] At present, the modification of high-nickel ternary materials mainly adopts bulk doping, surface coating, construction of radial distribution microstructure, full concentration gradient design and other methods to control the surface interface structure and bulk lattice regulation. However, these methods are still limited in improving the electrochemical performance of high-nickel materials. The main reasons are: ① Conventional coating methods usually introduce an oxide inert layer with low lithium ion conductivity, which is not conducive to interfacial charge transfer and will also lose part of the reversible capacity; ② Conventional coating methods are only based on simple blending, evaporation or hydrolysis of solid or liquid phases, lacking the means of kinetic control to construct a uniform coating layer with nanometer precision on the surface of the particles. The uncoated area will expose more reaction sites, resulting in poor protection effect; ③ High-nickel materials are very sensitive to moisture and air. The general water-based coating method will aggravate the corrosion and dissolution of active substances and the side reactions of residual lithium / bulk lithium on the surface with water and carbon dioxide in the solution and air, destroying the crystal structure and causing capacity loss; ④ There is a lack of effective methods for synchronously stabilizing the electrode / electrolyte interface and bulk lattice, and it is impossible to accurately control the surface interface structure. Summary of the invention

[0005] The purpose of the present invention is to provide a high-stability high-nickel ternary positive electrode material modified with aluminum and tantalum metals, and a preparation method and application thereof, so as to improve the stability and safety of existing high-nickel ternary positive electrode materials. The method provided by the present invention can not only realize the uniform and controllable coating of aluminum and tantalum metals on the surface of high-nickel ternary, but also the surface treatment process of the method can fully meet the needs of scaled-up production under the premise of ensuring that no additional damage is caused to the high-nickel ternary positive electrode material, and has the advantages of low cost and high reliability.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a positive electrode composite material, comprising the following components: a high-nickel ternary positive electrode material and a coating layer on its surface;

[0008] The structural formula of the high nickel ternary positive electrode material is LiNi x Co y Mn 1-x-y O2;

[0009] in:

[0010] 0.6≤x<1, illustratively, x=0.6, 0.7, 0.8, 0.91;

[0011] 0<y≤0.2, illustratively, y=0.06, 0.1, 0.2;

[0012] x+y<1;

[0013] The coating layer is a nano coating containing aluminum tantalum metal.

[0014] The high nickel ternary positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.91 Co 0.06 Mn 0.03 O2.

[0015] The high-nickel ternary positive electrode material is a single crystal material or a polycrystalline material.

[0016] In the positive electrode composite material, the mass fraction of aluminum element is 0.03-2%, preferably (0.3-0.9): 1, and exemplified by 0.05%, 0.1%, 0.5%, 0.8%, 1.0%, and 2.0%.

[0017] In the positive electrode composite material, the mass fraction of tantalum element is 0.05-1.8%, preferably (0.5-1.5): 1, and exemplified by 0.08%, 0.1%, 0.5%, 0.8%, 1.0%, and 1.5%.

[0018] The coating layer has a thickness of 0.5-30 nm, preferably 1-10 nm, and exemplified by 1 nm, 3 nm, 5 nm, 7 nm, and 9 nm.

[0019] In a second aspect, the present invention further provides a method for preparing the above-mentioned positive electrode composite material, comprising the following steps:

[0020] (1) dissolving a soluble organic aluminum salt, a soluble organic tantalum salt and a complexing agent in a non-aqueous solvent and stirring to obtain a solution A;

[0021] (2) taking another non-aqueous solvent, adding the high-nickel ternary positive electrode material and the alkaline solution into the non-aqueous solvent, and dispersing to obtain a suspension B;

[0022] (3) pouring the solution A into the suspension B, stirring, centrifuging, washing, and drying to obtain a material with an aluminum-tantalum modified surface;

[0023] (4) Calcining the material with the surface modified by aluminum tantalum to obtain a high-nickel ternary positive electrode material with surface modified by aluminum tantalum species, namely the positive electrode composite material.

[0024] In step (1), the soluble organic aluminum salt is one or more of aluminum alcoholate, aluminum acetylacetonate and aluminum ethoxylate; for example, aluminum alcoholate; illustratively, aluminum isopropoxide.

[0025] In the solution A, the concentration of the soluble organic aluminum salt is 1×10 -6 -10 mol / L, preferably 1×10 -4 -1mol / L, exemplified by 1×10 -4 mol / L、1×10 -3 mol / L, 0.01mol / L, 0.1mol / L, 1mol / L.

[0026] In step (1), the soluble organic tantalum salt is one or more of tantalum alcohol salts, tantalum acetylacetonate salts and tantalum ethoxide salts; for example, selected from tantalum alcohol salts; illustratively, selected from tantalum ethoxide salts.

[0027] In the solution A, the concentration of the soluble organic tantalum salt is 1×10 -6 -10 mol / L, preferably 1×10 -4 -1mol / L, exemplified by 1×10 -4 mol / L、1×10 -3mol / L, 0.01mol / L, 0.1mol / L, 1mol / L.

[0028] In step (1), the ligand is at least one of alkanoic acid, dilute acid, acetylic acid, alkylamine, dilute amine and acetylenic amine; for example, it can be selected from at least one of hexadecanethiol, n-pentanoic acid, n-octylamine, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, linoleic acid, eicosanoic acid, dodecylamine, tetradecylamine, hexadecylamine and the like.

[0029] In the solution A, the concentration of the complexing agent is 3×10 -6 -30mol / L, more preferably 3×10 -4 -3 mol / L, exemplified by 3×10 -4 mol / L、3×10 -3 mol / L, 0.03mol / L, 0.3mol / L, 3mol / L.

[0030] In step (1), the non-aqueous solvent is an anhydrous organic solvent, for example, selected from an anhydrous alcohol solvent and / or an anhydrous ketone solvent; preferably, the non-aqueous solvent is selected from at least one of methanol, anhydrous ethanol, isopropanol, n-propanol, ethylene glycol, propylene glycol, n-butanol and acetone; more preferably, it is anhydrous ethanol. Furthermore, the purity of the non-aqueous solvent is chromatographically pure, and its water content is ≤0.1wt%.

[0031] In step (2), the structural formula of the high nickel ternary positive electrode material is LiNi x Co y Mn 1-x-y O2; wherein: 0.6≤x<1, exemplarily, x=0.6, 0.7, 0.8, 0.91; 0<y≤0.2, exemplarily, y=0.06, 0.1, 0.2; x+y<1; preferably, the high nickel ternary positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.91 Co 0.06 Mn 0.03 O2.

[0032] The high-nickel ternary positive electrode material is a single crystal material or a polycrystalline material.

[0033] In the suspension B, the concentration of the high-nickel ternary positive electrode material is 0.001-1000 g / L; for example, the concentration is 0.05-50 g / L, 1-10 g / L; illustratively, the concentration is 2 g / L, 5 g / L, 8 g / L.

[0034] In step (2), the mass ratio of aluminum ions in the soluble organic aluminum salt, tantalum ions in the soluble organic tantalum salt and the high-nickel ternary positive electrode material is (0.03-2): (0.05-1.8): 1; preferably (0.3-0.9): (0.5-1.5): 1; exemplarily, the mass ratio is 0.5:0.8:1.

[0035] The alkali is one of ammonia water, sodium hydroxide or potassium hydroxide. The pH range of the alkali solution is preferably 8-10.

[0036] In step (3), the volume ratio of the solution A to the suspension B is 1:(1-300), preferably 1:(5-150).

[0037] The stirring conditions are: temperature of -10-80°C, preferably 20-30°C, exemplarily 25°C, time of 0.1-48h, preferably 0.5-3h, exemplarily 0.5h, 1h, 3h.

[0038] In step (4), the calcination conditions are: temperature of 300-1000°C, preferably 500-800°C, more preferably 550-650°C, exemplarily 500°C, 600°C, 700°C, 800°C; time of 0.5-24h, preferably 1-5h, exemplarily 1h, 1h, 3h, 5h.

[0039] The heating rate of the calcination is 1-10°C / min, exemplified by 1°C / min, 5°C / min, and 10°C / min.

[0040] In a third aspect, the present invention further provides a lithium-ion battery, comprising a positive electrode and a negative electrode; the material used for the positive electrode is the above-mentioned positive electrode composite material.

[0041] The positive electrode further includes a conductive agent and a binder; the conductive agent may be a common conductive agent, such as Super-P; the binder may be a common binder, such as polyvinylidene fluoride (PVDF).

[0042] In the positive electrode, the mass ratio of the positive electrode material to the conductive agent and the adhesive is (3-65):1:1, exemplarily 8:1:1.

[0043] The beneficial effects achieved by the present invention are as follows:

[0044] 1. The present invention is based on the reaction environment provided by the non-aqueous solvent, and while introducing aluminum-tantalum metal coating species on the surface of the positive electrode material, it can effectively avoid the damage of environmental water to the high-nickel ternary positive electrode material.

[0045] 2. Starting from the selection and control of coating species, the present invention is based on a low-cost and efficient surface treatment process, and further combined with the subsequent high-temperature heat treatment process, the chemical reaction between the surface coating species and the high-nickel positive electrode on the surface is regulated to obtain a positive electrode material modified with aluminum tantalum metal with structural stability, and the physical and chemical properties of the high-nickel positive electrode surface are regulated and optimized, thereby obtaining a highly stable positive electrode / electrolyte interface, and then showing better electrochemical stability during battery testing.

[0046] 3. The preparation method provided by the present invention has the advantages of simple process, low cost, environmental friendliness and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the X-ray diffraction (XRD) pattern of the high-nickel single crystal positive electrode material modified with aluminum-tantalum metal in Example 1.

[0048] Figure 2 This is a scanning electron microscope (SEM) image of the high-nickel single crystal positive electrode material modified with aluminum-tantalum metal in Example 1.

[0049] Figure 3 This is a transmission electron microscope (TEM) image of the high-nickel single crystal positive electrode material modified with aluminum-tantalum metal in Example 1.

[0050] Figure 4 This is a high-resolution electron microscopy (HRTEM) image of the high-nickel single crystal positive electrode material modified with aluminum-tantalum metal in Example 1.

[0051] Figure 5 This is an X-ray energy dispersive spectrum analysis (EDS) image of the high-nickel single crystal positive electrode material modified with aluminum-tantalum metal in Example 1.

[0052] Figure 6 It is a charge and discharge curve diagram of the high nickel ternary single crystal positive electrode material in Example 1 and the comparative example at a 0.1C rate.

[0053] Figure 7 It is the cycle diagram of the high nickel ternary single crystal positive electrode material in Example 1 and the comparative example at 1C rate. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0055] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0056] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.

[0057] Example 1

[0058] (I) Preparation of positive electrode materials

[0059] At 25°C, 20.4 mg aluminum isopropoxide and 37.5 μL tantalum ethoxide were dissolved in 1 ml anhydrous ethanol, 30 μL tetradecylamine was added, and the mixture was stirred to obtain a clear and transparent solution A. 1.95 g single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 600°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0060] In the positive electrode material obtained in this embodiment, the mass fraction of aluminum element is 0.5%, and the mass fraction of tantalum element is 0.8%.

[0061] (II) Structural and morphological characterization

[0062] The crystal structure of the positive electrode material prepared in the embodiment was analyzed by powder X-ray diffractometer (D8 Advance, Brune). The results are as follows: Figure 1 As shown in the figure, it can be seen that the positive electrode material prepared in this embodiment conforms to the diffraction peak of the layered ternary material and has no other impurity peaks, indicating that the material purity is relatively high.

[0063] The morphology of the cathode material prepared in the embodiment was further characterized by a scanning electron microscope (SEM-4800). Figure 2 As shown in the figure, it can be seen that after surface modification, the material maintains the single crystal LiNi 0.8 Co 0.1 Mn 0.1 Morphology of O2(NCM) positive electrode material.

[0064] The morphology of the high nickel ternary single crystal cathode material coated with aluminum tantalum metal before calcination was characterized by transmission electron microscopy (TEM-2100F). Figure 3 As shown in the figure, it can be seen that the thickness of the aluminum-tantalum metal coating layer is about 5nm.

[0065] Figure 4 This is a high-resolution electron microscopy (HRTEM) image of the high-nickel single crystal positive electrode material modified with aluminum-tantalum metal in Example 1. Figure 4 It can be seen that the coating layer formed by uniform deposition on the surface of the positive electrode material is in an amorphous state and does not affect the typical crystal structure of the positive electrode material.

[0066] Figure 5 This is the X-ray energy spectrum analysis (EDS) diagram of the high-nickel ternary single crystal positive electrode material coated with aluminum-tantalum metal before calcination. The results in the figure show that there is a uniform and continuous aluminum-tantalum metal coating layer on the surface of the high-nickel ternary single crystal positive electrode material.

[0067] (III) Battery assembly

[0068] 200 mg of the prepared positive electrode material was mixed with 25 mg of the binder polyvinylidene fluoride (PVDF) and 25 mg of the conductive agent Super-P, and about 200 μL of N-methylpyrrolidone (NMP) was added to prepare a slurry. The slurry was evenly coated on the aluminum foil with an aluminum foil as the current collector. The coating thickness was 2 μm, and the positive electrode film was obtained by vacuum drying at 80 ° C for 12 hours. The metal lithium sheet was used as the negative electrode, the polypropylene microporous membrane (Celgard 2400) was used as the separator, and 1 mol / L LiPF6 (EC: DMC: DEC = 1: 4: 2) was used as the electrolyte. The button battery was assembled in an argon-protected glove box.

[0069] (IV) Performance test

[0070] The assembled battery was tested on a Blue Electric charge and discharge tester with a constant current charge and discharge rate of 0.1C (1C = 200mA / g) and a charge and discharge range of 3.0-4.3V. The charge and discharge curve of the first cycle is shown in Figure 1. Figure 6 As shown in the figure, it can be seen that the discharge capacity of the NCM positive electrode material can reach 197mAh / g. The charge and discharge range is 3.0-4.3V, and the capacity retention rate after 100 cycles at 1C rate is 96% (as shown in Figure 2). Figure 7 This indicates that the positive electrode material has good cycle stability.

[0071] Example 2

[0072] (I) Preparation of positive electrode materials

[0073] At 25°C, 10.2 mg aluminum isopropoxide and 18.8 μL tantalum ethoxide were dissolved in 1 ml anhydrous ethanol, 30 μL tetradecylamine was added, and the mixture was stirred to obtain a clear and transparent solution A. 1.95 g single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 600°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0074] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0075] (III) Assembling of the battery (the specific steps are the same as those in Example 1).

[0076] (IV) Performance test (specific steps are the same as in Example 1).

[0077] Example 3

[0078] (I) Preparation of positive electrode materials

[0079] At 25°C, 40.8 mg of aluminum isopropoxide and 75 μL of tantalum ethoxide were dissolved in 1 ml of anhydrous ethanol, 30 μL of tetradecylamine was added, and the mixture was stirred to obtain a clear and transparent solution A. 1.95 g of single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 600°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0080] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0081] (III) Assembling of the battery (the specific steps are the same as those in Example 1).

[0082] (IV) Performance test (specific steps are the same as in Example 1).

[0083] Comparative Example 1

[0084] (I) Preparation of positive electrode materials

[0085] At 25°C, 20.4 mg of aluminum isopropoxide was dissolved in 1 ml of anhydrous ethanol, 30 μL of tetradecylamine was added, and the mixture was stirred to obtain a clear and transparent solution A. 1.95 g of single crystal LiNi was accurately weighed. 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 600°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0086] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0087] (III) Assembling of the battery (the specific steps are the same as those in Example 1).

[0088] (IV) Performance test (specific steps are the same as in Example 1).

[0089] Comparative Example 2

[0090] (I) Preparation of positive electrode materials

[0091] At 25°C, dissolve 37.5 μL of tantalum ethoxide in 1 ml of anhydrous ethanol, add 30 μL of tetradecylamine, and stir evenly to obtain a clear and transparent solution A; accurately weigh 1.95 g of single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 600°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0092] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0093] (III) Assembling of the battery (the specific steps are the same as those in Example 1).

[0094] (IV) Performance test (specific steps are the same as in Example 1).

[0095] Comparative Example 3

[0096] (I) Preparation of positive electrode materials

[0097] At 25°C, add 30 μL of tetradecylamine to 1 ml of anhydrous ethanol and stir to obtain a clear and transparent solution A. Accurately weigh 1.95 g of single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 600°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0098] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0099] (III) Assembling of the battery (the specific steps are the same as those in Example 1).

[0100] (IV) Performance test (specific steps are the same as in Example 1).

[0101] Comparative Example 4

[0102] (I) Preparation of positive electrode materials

[0103] At 25°C, 20.4 mg aluminum isopropoxide and 37.5 μL tantalum ethoxide were dissolved in 1 ml anhydrous ethanol, 30 μL tetradecylamine was added, and the mixture was stirred to obtain a clear and transparent solution A. 1.95 g single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 500°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0104] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0105] (III) Assembling of the battery (the specific steps are the same as those in Example 1).

[0106] (IV) Performance test (specific steps are the same as in Example 1).

[0107] Comparative Example 5

[0108] (I) Preparation of positive electrode materials

[0109] At 25°C, 20.4 mg aluminum isopropoxide and 37.5 μL tantalum ethoxide were dissolved in 1 ml anhydrous ethanol, 30 μL tetradecylamine was added, and the mixture was stirred to obtain a clear and transparent solution A. 1.95 g single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) was dispersed in 9 ml of anhydrous ethanol, and 100 μL of aqueous ammonia was added to obtain suspension B; solution A was poured into suspension B, and the mixture was stirred at 25°C for 1 hour. The positive electrode material powder was obtained by centrifugation, washing and drying; the powder was calcined at 700°C at a heating rate of 5°C / min in a tubular furnace under an oxygen atmosphere for 3 hours, and then naturally cooled to room temperature and ground with a mortar to obtain an aluminum-tantalum metal-modified positive electrode material.

[0110] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0111] (III) Assembling of the battery (the specific steps are the same as those in Example 1).

[0112] (IV) Performance test (specific steps are the same as in Example 1).

[0113] Effect verification

[0114] The performance test results of the batteries of Examples 1-3 and Comparative Examples 1-5 are shown in Table 1 below.

[0115] Table 1 Performance indicators of batteries prepared from materials obtained in Examples and Comparative Examples

[0116] First cycle discharge capacity (mAh / g) 100 cycles capacity retention rate (%) Example 1 195.6 96.5 Example 2 195.2 95.6 Example 3 194.5 96.0 Comparative Example 1 194.5 95.2 Comparative Example 2 193.8 94.7 Comparative Example 3 193.7 86.8 Comparative Example 4 193.9 94.8 Comparative Example 5 194.2 93.7

[0117] By comparing Examples 1-3, it can be seen that the coating amount of aluminum-tantalum species will affect the first-cycle discharge capacity and cycle stability of the positive electrode material. When the coating amount of aluminum-tantalum species is too low, as shown in Example 2, it is impossible to form a sufficient stable layer on the surface of the ternary positive electrode material, and thus it is impossible to fully protect the surface of the positive electrode material; but when the coating amount of aluminum-tantalum species is too high, as shown in Example 3, other unstable impurities will be formed on the positive electrode surface, which will lead to a decrease in the first-cycle discharge capacity of the positive electrode material and a deterioration in the cycle stability. Therefore, in the present invention, the preferred range of the mass ratio of aluminum element to positive electrode material is preferably (0.3-0.9):1, and the preferred range of the mass ratio of tantalum element to positive electrode material is preferably (0.5-1.5):1.

[0118] By comparing Example 1 with Comparative Examples 4-5, it can be seen that the calcination temperature will affect the first-cycle discharge capacity and cycle stability of the positive electrode material. When the calcination temperature is too low, as shown in Comparative Example 4, the solid phase reaction between the aluminum-tantalum coating layer and the surface of the positive electrode material is incomplete, resulting in limited improvement in the cycle performance of the positive electrode material; but when the calcination temperature is too high, as shown in Comparative Example 5, the crystal structure of the positive electrode material itself will be destroyed and harmful impurities will be generated, resulting in a decrease in the first-cycle discharge capacity of the positive electrode material. Therefore, the preferred range of the calcination temperature in the present invention is 550-650°C.

[0119] By comparing Examples 1-3 with Comparative Examples 1-3, it can be seen that the cycle stability of the positive electrode materials obtained in Examples 1-3 is higher than that in Comparative Examples 1-3, and the discharge specific capacity is not reduced, which shows that the cycle stability of the positive electrode material can be improved by modifying the surface of the material with aluminum tantalum metal, and the appropriate addition amount will not sacrifice its discharge specific capacity. In particular, in Example 1, the cycle performance and discharge specific capacity are significantly improved.

[0120] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A positive electrode composite material, comprising the following components: a high-nickel ternary positive electrode material and a coating layer on its surface; The structural formula of the high nickel ternary positive electrode material is LiNi x Co y Mn 1-x-y O2; in: 0.6≤x<1; 0<y≤0.2; x+y<1; The coating layer is a nano coating containing aluminum tantalum metal.

2. The positive electrode composite material according to claim 1, characterized in that: The high nickel ternary positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.91 Co 0.06 Mn 0.03 O2.

3. The positive electrode composite material according to claim 1 or 2, characterized in that: In the positive electrode composite material, the mass fraction of aluminum element is 0.03-2%, and the mass fraction of tantalum element is 0.05-1.8%; The coating layer has a thickness of 0.5-30 nm.

4. A method for preparing the positive electrode composite material according to any one of claims 1 to 3, comprising the following steps: (1) dissolving a soluble organic aluminum salt, a soluble organic tantalum salt and a complexing agent in a non-aqueous solvent and stirring to obtain a solution A; (2) taking another non-aqueous solvent, adding the high-nickel ternary positive electrode material and the alkaline solution into the non-aqueous solvent, and dispersing to obtain a suspension B; (3) pouring the solution A into the suspension B, stirring, centrifuging, washing, and drying to obtain a material with an aluminum-tantalum modified surface; (4) Calcining the material with the surface modified by aluminum tantalum to obtain a high-nickel ternary positive electrode material with surface modified by aluminum tantalum species, namely the positive electrode composite material.

5. The preparation method according to claim 4, characterized in that: In step (1), the soluble organic aluminum salt is one or more of an alcohol aluminum salt, an acetylacetonate aluminum salt, and an ethoxy aluminum salt; In the solution A, the concentration of the soluble organic aluminum salt is 1×10 -6 -10mol / L; The soluble organic tantalum salt is one or more of tantalum alcoholate, tantalum acetylacetonate and tantalum ethoxide; In the solution A, the concentration of the soluble organic tantalum salt is 1×10 -6 -10mol / L.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), in step (1), the complexing agent is at least one of alkanoic acid, dilute acid, acetylic acid, alkylamine, dilute amine and acetylenic amine; In the solution A, the concentration of the complexing agent is 3×10 -6 -30mol / L; The non-aqueous solvent is an anhydrous alcohol solvent and / or an anhydrous ketone solvent.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (2), the mass ratio of aluminum ions in the soluble organic aluminum salt, tantalum ions in the soluble organic tantalum salt and the high-nickel ternary positive electrode material is (0.03-2): (0.05-1.8): 1; The alkali is one of ammonia water, sodium hydroxide or potassium hydroxide.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (3), the stirring conditions are: temperature of -10-80°C and time of 0.1-48h.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (4), the calcination conditions are: temperature of 300-1000° C., time of 0.5-24 h; The heating rate of the calcination is 1-10°C / min.

10. A lithium ion battery comprising a positive electrode and a negative electrode; the material used for the positive electrode is the positive electrode composite material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Ce1-xZrxO2 nano solid solution homogenate modified lithium ion battery anode material and preparation method thereof

    CN106058241A

  • Preparation method and application of no-clean high-nickel single-crystal lithium nickel cobalt manganate positive electrode material

    CN111916724A

  • Tantalum aluminum lithium phosphate modified high-nickel positive electrode material, precursor and preparation method

    CN113471441A

  • Nickel-iron-manganese ternary layered positive electrode material and preparation method thereof

    CN116454251A

Cited By

  • Neodymium-copper-modified high-nickel ternary positive electrode material as well as preparation method and application thereof

    CN120581583A